2016
DOI: 10.1088/1054-660x/26/11/115601
|View full text |Cite
|
Sign up to set email alerts
|

Biospeckle technique for the non-destructive differentiation of bruised and fresh regions of an Indian apple using intensity-based algorithms

Abstract: In the present paper intensity-based algorithms have been applied to differentiate the bruised and fresh regions of an Indian apple through biospeckle technique during its 9 day shelf life. Existing algorithms such as the co-occurrence matrix, inertia moment, absolute value difference, generalized difference, parameterized Fujii, biospeckle activity (BA) value, granulometric size distribution (GSD) and grey-level co-occurrence matrix (GLCM), as well as three new proposed algorithms namely parameterized general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These measurements of biological activity during fruit development are the result of physicochemical variations that occur inside the cells, and such behavior of biological activity reduction may be caused by metabolic, enzymatic and respiratory activity that occur during the ripening process. Kumari & Nirala (2016) used the Biospeckle laser to differentiate fresh from damaged areas in apples. They found that the level of biological activity in both areas decreased as the maturation process evolved, which corroborates the results found in our paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These measurements of biological activity during fruit development are the result of physicochemical variations that occur inside the cells, and such behavior of biological activity reduction may be caused by metabolic, enzymatic and respiratory activity that occur during the ripening process. Kumari & Nirala (2016) used the Biospeckle laser to differentiate fresh from damaged areas in apples. They found that the level of biological activity in both areas decreased as the maturation process evolved, which corroborates the results found in our paper.…”
Section: Resultsmentioning
confidence: 99%
“…Among the many image processing methods, the generalized differences method (GD) has good qualitative results (Kumari & Nirala, 2016). The GD algorithm calculates the absolute sum of the intensity differences between an image and its subsequent one, identifying the luminous intensity of each component pixel, thus resulting in a new image, which the pixels with different intensities highlighted (Minz & Nirala, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Existing methods-GD, PGD and AGD methods. Spectral activity maps are also obtained using GD (Saúde et al 2012), PGD (Kumari and Nirala 2016) and AGD (Kumari and Nirala 2016) algorithms and they are given respectively as…”
Section: Methods Of Biospeckle Data Analysismentioning
confidence: 99%
“…SM index has been used to differentiate between bruised and fresh regions of Indian apples [16]. The algorithm is defined as…”
Section: Algorithms To Process Imagesmentioning
confidence: 99%